Combination of chemistry and material science to overcome health problems - Johannes Karges (Elsevier, 2022)
Since its outbreak, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has strongly influenced the life of the general public around the world. Based on its fast spread and high mortality, there is a need for novel therapeutic treatments to overcome this global health crisis. While medicinal chemistry is focused on the development of highly selective and affine inhibitors toward a specific target enzyme, material science is focused on the development of nanomaterials for selective drug delivery. Based on the individual strengths, these disciplines could synergistically act together and help overcome the limitations of the respective approach. Herein, the combination of medicinal chemistry with material science to overcome health problems with the example of SARS-CoV-2 is critically discussed.